Oxidative Stress Levels of Fine Particulate Matter (PM2.5) and Urinary Glutathione of Microbus Drivers - Sidebang, Purnama; Kusumayati, Agustin; Haryanto, Budi (UI Scholars Hub, 2023)
Urinary glutathione levels are known to be an early indicator of oxidative stress in travelers. This study analyzed the association between particulate matter (PM2.5) exposure on the road and urine glutathione levels in Jakarta’s microbus drivers. This cross-sectional study involved 96 microbuses (one of Jakarta’s public transportations) drivers of nine routes in Kampung Melayu Bus Station, Jakarta, Indonesia. An anthropometric assessment and a structured questionnaire were employed. Along with the participants driving on the road, real-time personal equipment measuring PM2.5 exposure concentrations was used. Total glutathione levels were measured using a colorimetric method. A correlation test and linear regression analysis were used to examine the effect of PM2.5 exposure on total glutathione levels. The average PM2.5 exposure concentration was 90.9±1.8 μg/m3, with a maximum concentration of 114.7 μg/m3. The average urinary glutathione level was 1.3±0.5 μM. The regression analysis showed that PM2.5 was associated with urinary glutathione levels after controlling for body mass index and smoking status. To conclude, the drivers experience exposure to an extremely high level of PM2.5 that could influence the glutathione levels.